First aid cooling techniques for heat stroke and exertional hyperthermia: A systematic review and meta-analysis. (1st March 2020) - ,; Borra, Vere; Carlson, Jestin N.; Cassan, Pascal; Charlton, Nathan P.; Markenson, David S.; Meyran, Daniel; Sakamoto, Tetsuya; Swain, Janel M.; Woodin, Jeff A.; Douma, Matthew J.; Aves, Theresa; et al.
Abstract: Background: Heat stroke is an emergent condition characterized by hyperthermia (>40 °C/>104 °F) and nervous system dysregulation. There are two primary etiologies: exertional which occurs during physical activity and non-exertional which occurs during extreme heat events without physical exertion. Left untreated, both may lead to significant morbidity, are considered a special circumstance for cardiac arrest, and cause of mortality. Methods: We searched Medline, Embase, CINAHL and SPORTDiscus. We used Grading of Recommendations Assessment, Development and Evaluation (GRADE) methods and risk of bias assessments to determine the certainty and quality of evidence. We included randomized controlled trials, non-randomized trials, cohort studies and case series of five or more patients that evaluated adults and children with non-exertional or exertional heat stroke or exertional hyperthermia, and any cooling technique applicable to first aid and prehospital settings. Outcomes included: cooling rate, mortality, neurological dysfunction, adverse effects and hospital length of stay. Results: We included 63 studies, of which 37 were controlled studies, two were cohort studies and 24 were case series of heat stroke patients. Water immersion of adults with exertional hyperthermia [cold water (14–17 °C/ 57.2–62.6 °F), colder water (8–12 °C/48.2–53.6 °F) and ice water (1–5 °C/ 33.8–41 °F) ] resulted in faster cooling rates when compared to passive cooling. No single water temperature range was found to be associated with a quicker core temperature reduction than another (cold, colder or ice). Conclusion: Water immersion techniques (using 1–17 °C water) more effectively lowered core body temperatures when compared with passive cooling, in hyperthermic adults. The available evidence suggests water immersion can rapidly reduce core body temperature in settings where it is feasible.